Instillation of students' moral values through habituation of religious programs at Madrasah Aliyah Negeri (MAN) Wonogiri, Indonesia - Sari, Dewi Novita; Abidin, Zaenal (Universitas Wiralodra, 2023)
Instilling students' moral values through religious programs at MAN Wonogiri is an educational effort that aims to form strong character and noble characters in students. This study explores how to instill the values of discipline and honesty in students through habituation of religious programs and how supporting and inhibiting factors in instilling the values of discipline and honesty in students through habituation of religious programs at MAN Wonogiri. This research is qualitative research on phenomenology. Data collection techniques in this study use observation, interviews, and documentation. The subjects in this study were the Principals and teachers of aqidah akhlak subjects. Data analysis techniques in this study use analysis models according to Miles and Huberman, namely collection, reduction, and conclusion drawing/verification. The results of this study highlight efforts to instill the value of discipline and honesty in students through religious programs at MAN Wonogiri. These efforts include providing an understanding of disciplinary material in Islamic teachings, the use of punishment and rewards in the process of developing student discipline and providing good examples. Contributing factors include teachers' active participation in religious activities and the motivation of fellow students, while constraints include limited space and students deliberately hiding during religious activities.